PENGARUH BOBOT BADAN TERHADAP KUALITAS DAN KUANTITAS SEMEN SAPI SIMMENTAL - M. Adhyatma; Isnaini Nurul; Nuryadi Nuryadi (TERNAK TROPIKA Journal of Tropical Animal Production, 2013)
This research was to compare semen quality and quantity of simmental cattle on thevariation of weight. The research used six heads of cattle. The method of this research wassurvey method and analyze data using variety analyzing method, thus would be continuedusing duncan test if there are present significan differences. Simmental cattle at mediumweight (840 and 846 kg) had more quality than other two groups of weight, which showedfrom highest scale of colour, and consistency. Simmental cattle at low weight (764 and 797 kg)showed a highest scale of pH and mass motility rather than other two groups of weight. Theresearch of quantity of Simmental cattle at medium weight (840 and 846 kg) group showedhighest scale of volume average at 8,5 ± 0,92 ml, individual motility average at 60,6 ± 7,95%and amount of motil spermatozoa average at 6.082,6 ± 1.204,06 (106) rather than other groups.Highest scale concentration had showed on low weight (746 and 797 kg) Simmental cattlegroup average at 1.355,7 ± 153,60 (106/ml). The high weight (942 and 952 kg) group ofSimmental cattle showed highest amount of spermatozoa average at 10.826,9 ± 1.777,16 (106).Simmental cattle at medium weight (840-846 kg) had better semen quality and quantity thanothers.Keywords : Simmental cattle, cattle weight, quality and quantity of semen